Basic Industry Strategy and Orientation Strategy - Maghfira, Maudy Priya; Yasin, Muhammad; Un, Alvine Wijana (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
This research is motivated by so much competition in a market orientation that is increasingly emerging, but competition sometimes pays little attention to product innovation in the eyes of consumers. The purpose of this study is to determine market orientation that occurs in the world of marketing, Entrepreneurial Orientation, Market Power as an independent variable, Marketing Performance as the dependent variable and Product Innovation as a mediating/intervening variable. The method used is the literacy method. The result of the research is that the basic industrialization strategy is an industrial strategy that focuses on the production of products and services for export, not for domestic sales and circulation. Consists of basic chemical industry and basic metal and machine industry. While the orientation industrialization strategy is the company's strategic direction in creating the right behavior so as to achieve superior performance. Market orientation as a process and activity related to creating and satisfying customers by continuously assessing customer needs and wants. Application of market orientation will bring increased performance for the company. Companies implementing market orientation have advantages in terms of customer knowledge and these advantages can be used as a source to create products that suit the wants and needs of customers.